Analisis Proses Degradasi Lahan dan Dampaknya Terhadap Produktifitas Lahan Pertanian di Kabupaten Klaten - Agus Anggoro Sigit; Suharjo Suharjo (Forum Geografi, 2007)
The aim of this research are : (1) identity the process of land degradation happened in the study area; (2) evaluation of agriculture land productivity with land degradation process in the study area; (3) analysis impact process of land degradation to agriculture land productivity in the study area. This research using survey method and spatial analysis by application of Geographical Information Sistem (GIS).According to data analysis, obtained by the following research result are: (1). Have been happened by process of land degradation in regional part of the study area which tend to degrade quality of land resources by type natural process influence (subsidence, slide, crack) and anthropogenic process (making of brick). Subsidence happened in Gantiwarno; crack in Gantiwarno and Bayat; slide in Bayat. Making o brick a lot of happened in Jogonalan, Ngawen, Jatinom, Karanganom and Ceper; (2). Region with compatibility ‘harmony’ in the study area take of area for the width of 28930,10 Ha or 44,13 % (regional half almost Klaten District of productivity of its rice crop as according to its land suitability); ‘harmony (-)’ taking of area for the width of 2973,15 Ha or4,53 % (there are partial; a little region in Klaten District which manifestly do not good for effort to agriculture of rice crop, specially the paddy); ‘not harmony (+)’ taking of area for the which of 7929,25 Ha or 12,10 % (there are some region in Klaten District bad its of land condition, but its productivity is goodness); ‘not harmony’ taking of area for the which of 25724,10 Ha or 39,24 % (there are region with big enough area in Klaten District which to make a effort of agriculture of its rice crop not yet been done in an optimal fashion). Region with compatibility ‘not harmony’ need deeper attention of its land management; (3). Land degradation of most be happened to regions with compatibility status ‘not harmony’. Although is not be absolute in character, but this matter represent and existence indication of s possibility of influence of land degradation to lowering mount land productivity to rice crop in the study area. Land degradation at region of have compatibility status  ‘harmony’ as in Gantiwarno (in this time) reality not yet affect its influence to level of land productivity for the rice crop.